Possibilities of Using the One-Page Profile in Education - Šeben Zaťková, Timea; Funk, Viktor; Bírová, Jana (Journal of Education Culture and Society, 2025)
Aim. The study explores the person-centred approach, its application in education, and the description of one-page profile (OPP) usage as a technique based on the approach as mentioned above. The study aims to investigate the strengths, needs, preferences, and desired support of students according to the data obtained from their OPP. Partial aims of the investigation are: a) To identify students´ interests and needs that are relevant to their learning. B) To explore the opportunities for supporting the students in their learning.Methods. The research design is qualitative, using document analysis as the research method. The one-page profiles created by students at the lower secondary level of education were analysed through content thematic analysis.Results. The results shed light on the students´ perceived A) strengths in terms of various personality qualities and special talents, B) students’ preferences connected to Social factors; Academic aspects; Interests; Material and financial aspects, C) expected support divided into support based on Social factors and Academic Aspects and support in competences and skills development (Quality Education, teaching methods).Conclusion. The brief conclusion of the possibilities of OPP in educational practice and the proposals for supporting the students in their learning and development are included in the text. Peer-to-peer tutoring, family support, smaller classes, qualified staff, teacher support, and school counselling are important implications arising from the data and information gathered from students' OPP.